2018
DOI: 10.1080/14397595.2018.1442171
|View full text |Cite
|
Sign up to set email alerts
|

A new assessment tool for ulnar drift in patients with rheumatoid arthritis using pathophysiological parameters of the metacarpophalangeal joint

Abstract: Our UD evaluation appeared to be simple and related to function. Additionally, it enables dividing UD hands into five stages. Thus, our assessment should be beneficial compared to the Fearnley classification in considering treatments of UD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…UD of the fingers was assessed based on four parameters of the MP joint (deviation, subluxation, reduction, and bone destruction) and was scored from zero to two for each parameter (Toyama et al., 2014, 2019). The degree of UD was evaluated based on the sum of each parameter score; the sum score increased in tandem with worsening of the UD.…”
Section: Methodsmentioning
confidence: 99%
“…UD of the fingers was assessed based on four parameters of the MP joint (deviation, subluxation, reduction, and bone destruction) and was scored from zero to two for each parameter (Toyama et al., 2014, 2019). The degree of UD was evaluated based on the sum of each parameter score; the sum score increased in tandem with worsening of the UD.…”
Section: Methodsmentioning
confidence: 99%
“…The ulnar drift total score was calculated by adding scores for the four parameters for the metacarpophalangeal joints (deviation, subluxation, reduction, and bone destruction) and was scored from 0 to 2 for each parameter. The severity of ulnar drift was evaluated according to the sum of each parameter's score, and scores increased with worsening of the ulnar drift [8].…”
Section: Deformity Evaluationmentioning
confidence: 99%
“…Another study described severity of deformity from a 5-year observation of established rheumatoid arthritis patients and found that overall deformities worsened with time [4]. The authors evaluated thumb deformity using the Nalebuff classification system (type 1-6) [5], finger swan-neck deformity using the Nalebuff classification (type 1-4) [6], finger boutonnière deformity using the Nalebuff classification (stage 1-3), and ulnar drift by the authors' new method [7], which quantified ulnar drift by evaluating joint parameters in an extended cohort [8].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, we completed a nal follow-up survey of 37 patients with 63 hands (2 men and 35 women) ( Fig. 1) [8].…”
Section: Patientsmentioning
confidence: 99%
“…Another study described the severity of deformity in a 5-year observation of established rheumatoid arthritis patients and found that overall deformities worsened with time [4]. The authors evaluated thumb deformity using the Nalebuff classi cation system (type 1-6) [5], nger swan-neck deformity using the Nalebuff classi cation (type 1-4) [6], nger boutonnière deformity using the Nalebuff classi cation (stage 1-3), and ulnar drift by the authors' own method [7], which quanti ed ulnar drift by evaluating joint parameters in an extended cohort [8].…”
Section: Introductionmentioning
confidence: 99%